A comparative analysis of the efficiency, timing, and permanence of CO2 removal pathways. Issue 10 (21st September 2022) - Chiquier, Solene; Patrizio, Piera; Bui, Mai; Sunny, Nixon; Mac Dowell, Niall
Abstract : Carbon dioxide removal (CDR) is essential to deliver the climate objectives of the Paris Agreement. Whilst several CDR pathways have been identified, they vary significantly in terms of CO2 removal efficiency, timing, and permanence. Abstract : Carbon dioxide removal (CDR) is essential to deliver the climate objectives of the Paris Agreement. Whilst several CDR pathways have been identified, they vary significantly in terms of CO2 removal efficiency, elapsed time between their deployment and effective CO2 removal, and CO2 removal permanence. All these criteria are critical for the commercial-scale deployment of CDR. In this study, we evaluate a set of archetypal CDR pathways—including afforestation/reforestation (AR), bioenergy with carbon capture and storage (BECCS), biochar, direct air capture of CO2 with storage (DACCS) and enhanced weathering (EW)—through this lens. We present a series of thought experiments, considering different climates and forest types for AR, land types, e.g. impacting biomass yield and (direct and indirect) land use change, and biomass types for BECCS and biochar, capture processes for DACCS, and rock types for EW. Results show that AR can be highly efficient in delivering CDR, up to 95–99% under optimal conditions. However, regional bio-geophysical factors, such as the near-term relatively slow and limited forest growth in cold climates, or the long-term exposure to natural disturbances, e.g. wildfires in warm and dry climates, substantially reduces the overall CO2 removal efficiency of AR. Conversely, BECCS delivers immediate and permanent CDR, but its CO2 removal efficiency can be significantly impacted by any initial carbon debt associated with (direct and indirect) land use change, and thereby significantly delayed. Biochar achieves low CDR efficiency, in the range of 20–39% when it is first integrated with the soil, and that regardless of the biomass feedstock considered. Moreover, its CO2 removal efficiency can decrease to −3 to 5% with time, owing to the decay of biochar. Finally, as for BECCS, DACCS and EW deliver permanent CO2 removal, but their CO2 removal efficiencies are substantially characterized by the energy system within which they are deployed, in the range of −5 to 90% and 17–92%, respectively, if currently deployed. However, the CDR efficiency of EW can increase to 51–92% with time, owing to the carbonation rate of EW.